2005
DOI: 10.1074/jbc.m412437200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Metal Ion Coordination and the Catalytic Mechanism of Sphingomyelinases D

Abstract: Sphingomyelinases D (SMases D) fromLoxosceles spider venom are the principal toxins responsible for the manifestation of dermonecrosis, intravascular hemolysis, and acute renal failure, which can result in death. These enzymes catalyze the hydrolysis of sphingomyelin, resulting in the formation of ceramide 1-phosphate and choline or the hydrolysis of lysophosphatidyl choline, generating the lipid mediator lysophosphatidic acid. This report represents the first crystal structure of a member of the sphingomyelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 47 publications
6
92
0
Order By: Relevance
“…This feature, not present in class I SMases D, diminishes significantly the active-site volume and also alters the inherent flexibility exhibited by the flexible loop. Beyond that, all the structural features observed in class I SMases D are fully conserved and details concerning the action mechanism are well described in Murakami et al, 2005 andMurakami et al, 2006. 3.6 Sphingomyelin-binding mode to SMases D Despite the structure of a SMase D member has been solved, there is neither structural nor biophysical data relating the binding mode of the sphingomyelinase (SM) into the active-site cleft of SMases D. Thus, in order to shed light into the structural determinants for recognition and binding of SM by SMases D, a MD simulation was performed using the crystal structure of the SMase D I and the SM docked into enzyme taking into account the crystallographic position of the sulphate ion, which provides a good notion how the phosphate group from SM is oriented in the active-site cavity.…”
Section: Overall Structure Descriptionmentioning
confidence: 98%
See 1 more Smart Citation
“…This feature, not present in class I SMases D, diminishes significantly the active-site volume and also alters the inherent flexibility exhibited by the flexible loop. Beyond that, all the structural features observed in class I SMases D are fully conserved and details concerning the action mechanism are well described in Murakami et al, 2005 andMurakami et al, 2006. 3.6 Sphingomyelin-binding mode to SMases D Despite the structure of a SMase D member has been solved, there is neither structural nor biophysical data relating the binding mode of the sphingomyelinase (SM) into the active-site cleft of SMases D. Thus, in order to shed light into the structural determinants for recognition and binding of SM by SMases D, a MD simulation was performed using the crystal structure of the SMase D I and the SM docked into enzyme taking into account the crystallographic position of the sulphate ion, which provides a good notion how the phosphate group from SM is oriented in the active-site cavity.…”
Section: Overall Structure Descriptionmentioning
confidence: 98%
“…L. adelaida SMase D A1 is a class II member and conserves all structural features for catalytic activity upon sphingomyelin. MD simulations indicated the binding mode of SM in the SMase I, a class I member that already has its crystallographic structure solved (Murakami et al, 2005) and they demonstrated the role exerted by Trp230 in the orientation of choline head, the magnesium ion in the coordination of the phosphate group and other aliphatic residues in the stabilization of substrate at the active site. In conclusion, we have cloned, expressed and biochemically and structurally characterized a new sphingomyelinase D from Loxosceles adelaida spider and shown that it displays all the functional characteristics of whole venom.…”
mentioning
confidence: 99%
“…4) (55). This type of SMase D lacks the HKD motif seen in phospholipase Ds (PLDs), explaining why they do not act on phosphatidylcholine (PC) and other glycerophospholipids, although sometimes they are mistakenly referred to as PLDs (56)(57)(58).…”
Section: Sphingomyelinase Ds Which Adopt a Tim Barrel Structurementioning
confidence: 99%
“…These bacterial proteins are homologous to enzymes from several fungi and from spiders of the Sicariidae family (54), such as the SMase I from Loxosceles laeta (PDB ID 1XX1) (55).…”
Section: Sphingomyelinase Ds Which Adopt a Tim Barrel Structurementioning
confidence: 99%
“…As some Loxosceles sphingomyelinases D have broad substrate specificity, being able to hydrolyze not only sphingophospholipids but also lysoglycerophospholipids, they are now classified as phospholipases D (Lee and Lynch, 2005). Due to sequence, structural and biochemical differences these toxins are grouped in two classes and their structures and substrate specificities have been recently elucidated (de Giuseppe et al, 2011;Murakami et al, 2005). Other important components of Loxosceles venom are the metalloproteinases.…”
Section: Loxosceles Venommentioning
confidence: 99%